2014
DOI: 10.1007/s00381-014-2416-5
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in the expression of miR-124-3p, miR-128-1, and miR-221-3p in pediatric astrocytomas are related to high-grade supratentorial, and recurrent tumors in Mexican children

Abstract: The low expression of these miRNAs may constitute a potential marker of astrocytomas that correlates with localization, possibly due to alterations in the maturation processes of these miRNAs that produced low mature forms in patients with recurrent pediatric astrocytomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Therefore, our finding of its involvement in CAD may provide novel evidence for deeper research in this area. MiR‐221‐3p was identified as a novel marker for an early prediction of acute myocardial infarction (AMI) in earlier reports, and the increased expression levels of this miRNA was also found in AMI patients, which was consistent with the finding in this study of its upregulation in CAD patients. Besides, it was found that the miRNA, which was previously upregulated, was significantly downregulated after the treatment of CAD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, our finding of its involvement in CAD may provide novel evidence for deeper research in this area. MiR‐221‐3p was identified as a novel marker for an early prediction of acute myocardial infarction (AMI) in earlier reports, and the increased expression levels of this miRNA was also found in AMI patients, which was consistent with the finding in this study of its upregulation in CAD patients. Besides, it was found that the miRNA, which was previously upregulated, was significantly downregulated after the treatment of CAD patients.…”
Section: Discussionsupporting
confidence: 91%
“…The antitumor effect of miR‐124‐3p in GBM cells is enhanced through gap junctions by partly decreasing CDK6 expression . Furthermore, miR‐124‐3p is associated with malignant tumor progression and poor prognosis in glioma patients and is related to recurrent high‐grade gliomas in Mexican children, indicating that miR‐124‐3p is a potential biomarker for glioma. Therefore, one miRNA can target multiple genes and affect various cellular pathways, and this study clearly showed that PIM1 is also a direct target gene of miR‐124‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-124-3p has been confirmed to be downregulated in glioma tissues, and loss of miR-124-3p is associated with high malignance and poor prognosis in patients with glioma [31, 32]. Furthermore, the relative levels of miR-124-3p in serum exosomes could serve as a complementary diagnostic biomarker, providing a minimally invasive and innovative tool to diagnose gliomas at their onset and predict metastases and glioma grading before surgery [33].…”
Section: Discussionmentioning
confidence: 99%